Behavioral Therapy for Rural Substance Abusers - Leukefeld, Carl G. (Book collections on Project MUSE., 2015)
The problems and needs of rural substance abusers vary from those of abusers in urban areas. Accordingly, the means of treatment must acknowledge and address these differences. Despite this call for specialized care, no theoretically grounded therapy has yet been made available to rural patients. Behavioral Therapy for Rural Substance Abusers, developed and piloted over three years by University of Kentucky faculty and staff and substance abuse counselors in rural eastern Kentucky, provides a model for effective treatment for this segment of the population. A two-phase outpatient treatment, th.